Study of non-premixed turbulent flame of hydrogen/air downstream Co-Current injector. (8th February 2018) - Alliche, Mounir; Chikh, Salah
Abstract: For three decades, hydrogen has been identified as a versatile potential fuel concurrent to the conventional fuel such as gasoline. In order to fully implement it and to develop the combustion based power devices that may supply much higher energy density, it is very essential to understand the mechanism of Hydrogen/Air combustion. In this work, Computational Fluid Dynamics (CFD) numerical simulations have been performed to study the combustion of non-premixed turbulent hydrogen-air mixture with different equivalence ratios and different mass flow rates and its effect on different species formation, peak temperature and NOx formation. The performance of the combustor is evaluated by using FLUENT software under adiabatic wall condition. Generalized finite rate chemistry model was used to analyze the hydrogen-air combustion system. The combustion is modeled using multi-step reaction mechanism with 14 species, until complete conversion of fuel to H2 O. Through such a systematic analysis, a proper controlled operation condition for the combustor is suggested which may be used as a guideline for combustor design. Results reported in this work illustrate that the CFD simulation can be one of the most powerful, beneficial and economical tool for combustor design and for optimization and performance analysis. They are more sensitive to the model of the transport properties while the reasonable results can be achieved even with the use of global reaction mechanism and a simple turbulence model as k- ε, which are not excessively time and memory consuming. From an environmental point view, this study shows that the radical production (OH and NO) is very small although maximum temperature reached exceeded 2000 (K). The mass fraction of NO is much lower if we increase the air inlet velocity, which makes the cold reaction mixture do not promote the NO formation by dissociation. Highlights: Coupling thermochemical and turbulence in hydrogen combustion study. Effect of reaction mechanism on hydrogen flame properties. Research of the optimal choice of parameters in the burner using hydrogen as fuel. Effect of inlet conditions on NO mass fraction investigated.